2015
DOI: 10.1016/j.amepre.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Cancer Survivorship Activities for Comprehensive Cancer Control

Abstract: This report provides examples for incorporating cancer survivorship activities within Comprehensive Cancer Control programs of various sizes, demographic makeup, and resource capacity. New Mexico, South Carolina, Vermont, Washington state, and Fond Du Lac Band developed creative cancer survivorship activities that meet CDC recommendations. NCCCP grantees can follow these examples by implementing evidence-based survivorship interventions that meet the needs of their specific populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This finding is significant since emotional support at work can improve well-being and the overall return to work experience (Bloom, Stewart, Johnston, Banks, & Fobair, 2001;Nachreiner et al, 2007;Taskila et al, 2006). It is suggested that emotional support should be offered ongoingly to adapt to cancer survivors' changing needs at work (Underwood et al, 2015).…”
Section: Chapter 5: Discussionmentioning
confidence: 94%
“…This finding is significant since emotional support at work can improve well-being and the overall return to work experience (Bloom, Stewart, Johnston, Banks, & Fobair, 2001;Nachreiner et al, 2007;Taskila et al, 2006). It is suggested that emotional support should be offered ongoingly to adapt to cancer survivors' changing needs at work (Underwood et al, 2015).…”
Section: Chapter 5: Discussionmentioning
confidence: 94%
“…A recent assessment of the implementation of NAPCS revealed that 64% of NCCCP grantees include NAPCS strategies in their own program action plans . For example, grantees in New Mexico, South Carolina, Vermont, and Washington state and from the Fond Du Lac tribe have each implemented activities in all 4 of the NAPCS's strategy areas …”
Section: Cancer Control Programsmentioning
confidence: 99%
“…22 For example, grantees in New Mexico, South Carolina, Vermont, and Washington state and from the Fond Du Lac tribe have each implemented activities in all 4 of the NAPCS's strategy areas. 23 Survivorship care plans were identified by the Institute of Medicine for patients and their providers. 24 As people can live long after a cancer diagnosis, providing a summary of each cancer patient's treatment is an essential part of developing a complete survivorship care plan.…”
Section: National Comprehensive Cancer Control Programmentioning
confidence: 99%
“…[57] which encourages exercise among survivors, and the fielding of needs assessments to determine where to allocate resources to ensure access to quality care and services [56]. Specific examples of activities in New Mexico, South Carolina, Vermont, Washington state, and the Fond Du Lac Band of Lake Superior Chippewa tribe are: (1) promotion of doctor and patient use of survivor care plans to better understand care prescribed and received; (2) use of patient navigation programs to help survivors gain access to clinical services; (3) use of psychosocial distress screening among cancer survivors to identify and treat concurrent illnesses stemming from their cancer diagnosis; and (4) facilitation of communication among cancer survivors through peer support groups and workshops to help survivors feel less marginalized and better equipped to handle their diagnosis [58].…”
Section: Addressing the Public Health Needs Of Cancer Survivorsmentioning
confidence: 99%